ANALISIS POTENSI PAJAK DAN RETRIBUSI DAERAH DALAM PENINGKATAN PENDAPATAN ASLI DAERAH PROVINSI KALIMANTAN SELATAN - Rizky Amalia (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
This study aims to analyze how the contribution made by local taxes and levies to increase the Regional Original Income (PAD) of South Kalimantan. This study explains what efforts the government has made to optimize the regional income of South Kalimantan province. This research is an analysis of the contribution of local taxes and levies and the data analysis technique used to calculate the contribution of local taxes and levies is to compare the amount of local tax and levies revenues with the total local revenue. To increase the contribution of regional tax revenues and local levies to total PAD revenues and at the same time enlarge their contribution to the Regional Budget of the South Kalimantan’s government, several steps need to be taken, including increasing the intensification of collection of local taxes and levies, then extensification by imposing types of taxes and new levies in accordance with existing conditions and potential